PENGARUH NILAI PELANGGAN DAN RELATIONSHIP MARKETING TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA PT. TOYOTA HADJI KALLA KENDARI - Cahya Dwi Saputra; Yusuf Yusuf; Nofal Nur; Agustinus Tangalayuk; Isalman Isalman (Jurnal Manajemen dan Kewirausahaan, 2022)
The aim of this study; (1) To determine the effect of customer value on customer satisfaction at PT. Toyota Haji Kalla; (2) the influence of relationship marketing on customer satisfaction; (3) the influence of customer value on customer loyalty; (4) the influence of relationship marketing on customer loyalty; (5) the effect of customer satisfaction on customer loyalty; (6) the effect of customer value on customer loyalty through satisfaction as a mediating variable; (7) To determine the effect of marketing relationship on customer loyalty through satisfaction as a mediating variable. The population in this study were all customers of PT. Toyota Hadji Kalla made the purchase. The total population in this study cannot be known (infinitive). The sample of this study was 100 respondents using the Lemeshow formula. The results showed that: (1) Customer value had a significant effect on customer satisfaction at PT. Toyota Haji Kalla; (2) Relationship marketing has a significant effect on customer satisfaction; (3) Customer value has a significant effect on customer loyalty; (4) Relationship marketing has a significant effect on customer loyalty; (5) customer goals are significant to customer loyalty; (6) Customer value has a significant effect on customer loyalty through satisfaction as a mediating variable; (7) Relationship marketing has a significant effect on customer loyalty through satisfaction as a mediating variable